A major practicum report at Kanegie Food , Km 9 Barrio Pampanga, Sasa, Davao City - Alferez, Kate Pardinas (2007)
The 288 hr plant practice was conducted at Karnegie Food, Km. 9 Barrio Pampanga, Sasa, Davao City from April 18 to May 25, 2006. Their main products are Pre-mix of Native Delicacies and Food Flavorings. For 288 hr, the student was directly involved in receiving of the raw materials, processing line, packaging and research and development. She was also able to make a technical analysis about the whole plant operation and was able to identify some problems observed and presented recommendations to address them hopefully to improve the plant operations. The activities inside and outside the plant provided an opportunity to develop and establish interpersonal relations with personnel of the community and with my co-trainee